2018
DOI: 10.1021/acs.jpcb.8b01778
|View full text |Cite
|
Sign up to set email alerts
|

Tetronic Star Block Copolymer Micelles: Photophysical Characterization of Microenvironments and Applicability for Tuning Electron Transfer Reactions

Abstract: Detailed photophysical investigations have been carried out using a probe dye, coumarin-153 (C153), to understand the microenvironments of micelles formed by the newly introduced Tetronic star block copolymers, T1304 and T1307, having the same poly(propylene oxide) (PPO) block size but different poly(ethylene oxide) (PEO) block sizes. Ground state absorption, steady-state fluorescence, and time-resolved fluorescence measurements have been used to estimate the micropolarity, microviscosity, and solvation dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 76 publications
5
30
0
Order By: Relevance
“…Tetronics are a closely related class of BCPs, which share the same constituent blocks but with a four-arm star architecture. Tetronic 904 micelles have been shown to encapsulate drug molecules and have been characterized with respect to their size, aggregation number, and shell solvation in aqueous solution. ,,, The basicity of the central ethylene diamine unit underlies the advantageous pH-responsive self-assembly of the Tetronics. , Other notable applications of the Tetronics include their ability to control electron transfer reactions, their inhibitory action against ATP-binding cassette transporters in cancer cell lines, and their ability to disperse graphene at high concentration in solution, which may prove useful in processing technologies and new biomedical applications . While only limited simulation studies of the Tetronics have been reported in the literature to date, a variety of different simulation techniques have been used to study the micellization of a wide variety of other star-shaped amphiphilic BCPs. …”
Section: Introductionmentioning
confidence: 99%
“…Tetronics are a closely related class of BCPs, which share the same constituent blocks but with a four-arm star architecture. Tetronic 904 micelles have been shown to encapsulate drug molecules and have been characterized with respect to their size, aggregation number, and shell solvation in aqueous solution. ,,, The basicity of the central ethylene diamine unit underlies the advantageous pH-responsive self-assembly of the Tetronics. , Other notable applications of the Tetronics include their ability to control electron transfer reactions, their inhibitory action against ATP-binding cassette transporters in cancer cell lines, and their ability to disperse graphene at high concentration in solution, which may prove useful in processing technologies and new biomedical applications . While only limited simulation studies of the Tetronics have been reported in the literature to date, a variety of different simulation techniques have been used to study the micellization of a wide variety of other star-shaped amphiphilic BCPs. …”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic block copolymers are commercially available as Pluronics® (linear) and Tetronics® (star‐shaped). Generally, these copolymers are configured as two irreconcilable polymer segments, hydrophobic poly(propylene oxide) (PPO) and hydrophilic poly(ethylene oxide) (PEO), that vary in structure and molecular characteristics . The block copolymers aggregate and form nano‐scale core–shell micelles and sometimes vesicles (also called polymersomes) in analogy to conventional surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembly and structural versatility of amphiphilic block copolymers are active areas of research with extensive technological applications. Micelles formed with block copolymers have several advantages over those formed with conventional low-molecular weight surfactants. Some of the favorable attributes of polymeric micelles include lower critical micelle concentration (CMC), greater stability, core–shell structures with enhanced drug loading capacity, and better therapeutic potential and stimulus response. The poloxamine copolymers (Tetronics) consisting of an ethylene diamine group linked to four arms of repeating ethylene oxide (EO) and propylene oxide (PO) units are especially an interesting class of amphiphiles. Micelles formed with these star-shaped block copolymers are not only susceptible to temperature changes but also sensitive to pH of the medium. The central diamine group in Tetronic copolymers allows introduction of positive charges in these nonionic surfactants by protonation. The ensuing Coulombic repulsion between protonated amine groups perturbs the self-assembly of star block copolymers and disrupts micelle formation in acidic pH.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when the donor and acceptor are confined in micelles, their free diffusion is prevented, and bimolecular ET reactions proceed like intramolecular ET reactions, between suitably placed donor–acceptor pairs. Furthermore, since solvation dynamics is slower in micelles than in homogeneous solvents, the solvent reorganization energy (λ s ) cannot contribute completely in micellar media. , This effectively lowers the total reorganization energy, λ, and facilitates in attaining the condition of −Δ G 0 = λ, at lower exergonicities. The restricted diffusion of reactants and the lowering in effective reorganization energy, λ, make it possible to observe the MI behavior for bimolecular ET reactions in micellar media. The correlation between k obs and Δ G 0 for the bimolecular ET reaction in conventional solvents (RW behavior) and micelles (MI behavior) is depicted in Scheme .…”
Section: Introductionmentioning
confidence: 99%